Aplikasi Dynamic Factor Model untuk Nowcasting Pertumbuhan Ekonomi Regional Menggunakan Data Google Trends di Indonesia - Jesica Nauli Br. Siringo Ringo; Anugerah Karta Monika (Politeknik Statistika STIS, 2021)
Economic activity data is urgently needed to take various policies, but the data publication is experiencing delays. Gross Domestic Regional Product (GDRP) will be released within five weeks after the quarter ends. Nowcasting is an attempt to provide this data. Nowcasting is a method of forecasting the current period using higher frequency variables. Google Trends is high frequency data that is available in real time. This study aims to nowcast GDRP growth using Google Trends data. The nowcasting method used in this study is Dynamic Factor Model (DFM). Nowcasting results show that the model is able to capture the recent downturn in economic activity since the COVID-19 pandemic. The evaluation of the models between two data ranges shows that DFM is better in the data range that does not include periods of economic shock.